2016
DOI: 10.1007/s00417-016-3472-1
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, 12-month randomized study comparing dexamethasone intravitreal implant with ranibizumab in patients with diabetic macular edema

Abstract: Both DEX implant and ranibizumab were well tolerated and improved BCVA and anatomic outcomes in patients with DME. DEX implant met the a priori criterion for noninferiority to ranibizumab in average change from baseline BCVA over 12 months. Noninferiority was achieved with an average of 2.85 DEX implant injections and 8.70 ranibizumab injections per patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 33 publications
4
72
1
4
Order By: Relevance
“…Both treatments are well tolerated and improved BCVA and anatomic outcomes in patients with DME [13]. The combination of the 2 treat- ments can be of greater benefit to the patient, acting from the initial stages of the disease on the various mechanisms involved in its development, minimizing the possibility of monotherapy long-term side effects, and decreasing the amount of total injections required.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatments are well tolerated and improved BCVA and anatomic outcomes in patients with DME [13]. The combination of the 2 treat- ments can be of greater benefit to the patient, acting from the initial stages of the disease on the various mechanisms involved in its development, minimizing the possibility of monotherapy long-term side effects, and decreasing the amount of total injections required.…”
Section: Discussionmentioning
confidence: 99%
“…A direct comparison between the dexamethasone implant and ranibizumab (0.5 mg) has been published recently [3]. In this study, the dexamethasone implant injected in a fixed regimen every 5 months was compared with ranibizumab given monthly for at least the first three assessments.…”
Section: Comparison Of the Dexamethasone Implant And Anti-vegf Therapmentioning
confidence: 99%
“…Thus, different regimens have been used that reduce the number of injections and medical visits, although they are often accompanied by a decrease in efficiency compared to more intensive treatments. By contrast, the fixed regimens employed with the dexamethasone implant in clinical trials [2, 3] may not render optimal clinical outcomes, and a pro re nata approach has been suggested to try to maximize the functional results while minimizing the burden of visits [4]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, the FAME Study reported that a 140-μm reduction of the CRT was obtained 6 months after treatment with fluocinolone acetonide vitreous inserts [23, 24]. This led to an early and rapid reduction of the CRT and improvement of the BCVA in DME patients [25].…”
Section: Discussionmentioning
confidence: 99%